Searching for odd perfect numbers - Cruz, Christopher Thomas R. (Animo Repository, 2006)
An integer n is said to be perfect if (n) = 2n, where (n) denotes the sum of the positive divisors of n. There are no known odd perfect numbers yet. This paper presents some approaches in finding odd perfect numbers, and a proposed hypothesis that may lead to disprove their existence. Evaluating an odd perfect numbers upper bound and its total number of prime factors, denoted by (n), will provide key contributions to this hypothesis.